A virtual exchange experience: Preparing pre-service teachers for cultural diversity. Issue 3 (3rd July 2022) - Jaramillo Cherrez, Nadia; Gleason, Benjamin
Abstract: This study examines the experiences of 36 pre-service teachers from a large university in the midwestern U.S who participated in a 3-week virtual exchange with peers in Turkey. Drawing from a critical cosmopolitanism framework, we center these experiences to analyze the feelings, perspectives, assumptions, and growth engendered through the virtual exchange. Data was collected through journals and interpretation developed from an iterative content analysis. Findings suggested that pre-service teachers, and their Turkish peers, used a range of digital tools to lead to educational outcomes, including intercultural and personal discoveries, as well as a professional orientation to global interactions. These outcomes also indicated broader tensions that emerged, including some deficit-oriented perceptions of their peers. We argue that future virtual exchanges might benefit from a critical cosmopolitan approach based on emerging linguistic, intercultural, and intrapersonal dimensions which may counter hegemonic power positions and attitudes.